2018
DOI: 10.1038/s41401-018-0168-6
|View full text |Cite
|
Sign up to set email alerts
|

Propofol decreases the excitability of cholinergic neurons in mouse basal forebrain via GABAA receptors

Abstract: Propofol is an intravenous anesthetic that can active γ-aminobutyric acid A (GABA A) receptors and generate sedative-hypnotic effects. Propofol has been widely applied clinically to achieve sedation comparable to sleep in humans. The basal forebrain (BF) is a brain region that plays an important role in sleep-wake regulation. Previous studies suggest that propofol affects the sleep-wake circuit via the BF; however, the mechanism remains elusive. In the current study we investigated the effects of propofol on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…It is also worth noting that a majority of studies have focused on the mechanistic role of AMPARs and NMDARs in regulating LHb physiology, however there are a paucity of studies regarding how GABAARs are involved. Unlike other structures where exposure to propofol decreases neuronal excitability [35,36], this does not seem to be the case here. Interestingly, direct intra-LHb injections of GABAergic agonists and antagonists have been shown to decrease and increase LHb activity [37], respectively, indicating that GABAARs do indeed serve an inhibitory role within the LHb.…”
Section: Discussioncontrasting
confidence: 74%
“…It is also worth noting that a majority of studies have focused on the mechanistic role of AMPARs and NMDARs in regulating LHb physiology, however there are a paucity of studies regarding how GABAARs are involved. Unlike other structures where exposure to propofol decreases neuronal excitability [35,36], this does not seem to be the case here. Interestingly, direct intra-LHb injections of GABAergic agonists and antagonists have been shown to decrease and increase LHb activity [37], respectively, indicating that GABAARs do indeed serve an inhibitory role within the LHb.…”
Section: Discussioncontrasting
confidence: 74%
“…In spite of this, the event of BF cholinergic neurons is rapidly and continuously inhibited during propofol anesthesia. A study on brain slices also confirmed that propofol could decrease the excitability of cholinergic neurons in the basal forebrain of mouse (Chen et al, 2019). These results suggest that the BF cholinergic system might serve as a critical target for the function of general anesthetics.…”
Section: Discussionmentioning
confidence: 67%
“…We previously found that the activity of cholinergic neurons in BF could influence propofol and isoflurane anesthesia process 16 . Furthermore, several studies have indicated that propofol decreases the activity of BF cholinergic neurons via GABA A receptors 17,18 …”
Section: Introductionmentioning
confidence: 99%